Global lokalisering: Google Earth och upplevelsen av platsbundenhet i GeoGuessr, Houellebecq och Darrieussecq - Marcus, Gustaf (Tidskrift för litteraturvetenskap, 2024)
Global localization. Google Earth and the experience of place attachment in GeoGuessr, Houellebecq and Darrieussecq The purpose of this article is to analyze literary texts and other cultural practices that relate to or use content from Google Earth and, more generally, to outline what I call a contemporary glocal experience of place. The article discusses the browser game GeoGuessr and the interactive music video “The Wilderness Downtown” by Arcade Fire, along with the novel La Mer à l’envers by Marie Darrieussecq, and different works, including photographs and poems, by Michel Houellebecq. In all these instances, the transmissions, slippages, and tensions between a situated and embodied experience of place and global technological systems play a prominent role. The article shows how GeoGuessr and “The Wilderness Downtown” explore this tension from opposite points of departure: while the game fosters a sense of place within locales that are essentially unknown to the player, the music video integrates images from places that are related to the viewer’s personal memories into an otherwise impersonal animated video. In turn, Darrieussecq’s novel combines and narrativizes these opposing perspectives. Here, Calais represents a globalized space that can only be understood through glocalizing technologies, such as geoposititioning and interactive mapping. But Clève, the hometown of the protagonist, becomes unmoored through the same interaction with these technologies. Finally, the article highlights the “Houellebecq perspective” in novels, poems, and photographs. In these recurring scenes, the world is seen from above (through satellite imagery, on maps, or through airplanes windows). They revolve around the tension between the aerial view and the “horizon structure”, which permits the subject to place itself in the world and in relation to others.